Review of Air Intake System Development for Internal Combustion Engine - Yulia Ayu Nastiti; Nur Hidayatur R; Risma Nurdinda (Fakultas Teknik, 2022)
Today air intake system for internal combustion engines has experience changes to increase its performance. In existence of an appropriate air supply will affect the air-fuel ratio (AFR) and impact on the power generated and decrease the value of NOx for more complex effects. The increasing demand for energy encourages the creation of new technologies that increase the value of work in the form of decreasing emissions, increasing efficiency to longer durability. The method used in this study is a comparison of the results of each starting air system. The air intake system functions as an air supply for the combustion process, the first air intake system utilizing atmospheric pressure to push air into the combustion chamber which today has developed with a turbo system. Turbo system has functions to increase the amount of air supply and compress it, so that the combustion process will be more efficient and produce more environmentally friendly exhaust gases and more optimal power, in other words better efficiency this is known as a turbocharger.